Parent-Adolescent Communication Quality and Life Satisfaction: The Mediating Roles of Autonomy and Future Orientation - Bi X; Wang S (Psychology Research and Behavior Management, 2021)
Xinwen Bi, Shuqiong Wang Department of Education, Shandong Women’s University, Jinan, Shandong Province, People’s Republic of ChinaCorrespondence: Shuqiong WangDepartment of Education, Shandong Women’s University, Jinan, Shandong Province, People’s Republic of ChinaTel +86-18653143970Email qiongshuw1982@163.comBackground: Previous studies have suggested that family communication quality is an important factor that can influence adolescents’ life satisfaction. However, relatively few studies have examined this relationship in the Chinese cultural context or explored the potential mechanisms underlying this relationship. Therefore, the purpose of this study was to investigate whether family communication quality is closely linked to Chinese adolescents’ life satisfaction and whether this link was mediated by autonomy and future orientation.Methods: This study recruited 442 Chinese college students (67.19% girls) as participants. Based on a longitudinal design, the participants reported family communication quality at Time 1 and reported autonomy, future orientation, and life satisfaction at Time 2.Results: The results of correlation analysis showed the existence of a positive correlation between family communication quality, autonomy, future orientation, and life satisfaction. The mediation models showed family communication quality predicted adolescents’ life satisfaction through the mediating effects of autonomy and future orientation. Furthermore, autonomy and future orientation not only independently mediated the relationship between family communication quality and life satisfaction but sequentially mediated this relationship.Conclusion: Autonomy and future orientation mediated the relationship between family communication quality and life satisfaction. The findings of the present study highlight the significance of elevating family communication quality and promoting adolescents’ development of autonomy and future orientation to enhance their life satisfaction.Keywords: family communication, life satisfaction, autonomy, future orientation, adolescence